What opportunities are available for Nepalese Psychiatrists in the UK? (Journal of Psychiatrists' Association of Nepal, 2024)
This educational article highlights the opportunities available for Nepalese psychiatrists in the United Kingdom. Many psychiatrists from Nepal have relocated to the United Kingdom through different routes. A discussion was held among the authors to explore these routes and opportunities. The Royal College of Psychiatrists’ exam and sponsorship programs, including the Royal College of Psychiatrists’ Medical Training Initiative (MTI) and International Fellowship Programme are reviewed in detail.